A perspective of nursing students on the challenges of online learning in the blended learning era: a call to action for universities? - Rebekka Ndatolewe Gabriel; Valerie Nyahwema (Discover Education)
Abstract Blended learning has become the new norm post the pandemic. It aims to combine the advantages of online and face-to-face learning. However, the online aspect comes with unique challenges, some of which might be a spillover from the pandemic. This study explores the challenges nursing students face in adopting online learning within a blended learning environment, using the Technology Acceptance Model (TAM) as a theoretical lens. A qualitative, descriptive research design was employed, with data collected through Focus Group Discussions (FGDs) involving 40 undergraduate nursing students. Thematic analysis revealed key barriers to online learning: (1) digital illiteracy and lack of technological competence, (2) technical and infrastructure challenges, (3) financial constraints, and (4) psychological factors, such as isolation and mental fatigue. These challenges were mapped onto TAM components, where low perceived ease of use stemmed from platform navigation difficulties and unstable internet, while low perceived usefulness arose from students’ struggles to see online learning’s value amidst poor institutional support. The study recommends targeted digital literacy training, subsidized internet access, and mental health resources to enhance students’ readiness and willingness to adopt online learning. A multisectoral approach, involving universities, policymakers, and tech providers, is essential to bridge digital divides and optimize blended learning outcomes.